IDNLearn.com is your go-to resource for finding expert answers and community support. Join our community to receive prompt, thorough responses from knowledgeable experts.
Sagot :
Answer:
[tex]1 - 3x = 3x + 1 \\ 3x + 3x = 1 - 1 \\ 6x = 0 \\ \\ x = \frac{0}{6} \\ \\ x = 0[/tex]
I hope I helped you^_^
Answer:
x = 0
Step-by-step explanation:
1 - 3x = 3x + 1 ( subtract 3x from both sides )
1 - 6x = 1 ( subtract 1 from both sides )
- 6x = 0 , then
x = 0
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is your go-to source for accurate answers. Thanks for stopping by, and come back for more helpful information.